Atmospheric humidity and genotype are key determinants of the diurnal stomatal conductance pattern. (12th November 2019) - Zhang, Xinying; Wang, Yajing; Huang, Guirong; Feng, Fu; Liu, Xiaoying; Guo, Rui; Gu, Fengxue; Hu, Xin; Yang, Ziguang; Zhong, Xiuli; Mei, Xurong
Abstract: Great understanding of the genotypic difference in diurnal stomatal conductance ( g s ) pattern and the key determinants of the pattern is important for saving water by adopting cultivars appropriately. Fifteen wheat genotypes were studied under different soil conditions and various meteorological conditions with pot cultivation in rain shelter for two years. Genotype and air humidity were found to be key determinants of diurnal g s pattern. All genotypes under low relative humidity (LRH) and most genotypes under high relative humidity (HRH) displayed a gradual decline pattern from morning through the afternoon. Under moderate relative humidity (MRH), all genotypes present a single‐peak curve pattern, but they differed in peak time, which may lead to unreliable g s comparison between genotypes and get ostensible contrasting materials. The stomatal conductance was significantly different among genotypes under LRH and the increased g s magnitude is also significantly different when it was compared between LRH and HRH. The present results provide new thinking for selecting and adopting appropriate cultivars with specific stomata traits for the area with various meteorological conditions.